Block copolymer additives for toughening 3D printable epoxy resin - Ri Chen; Jizhe Cai; Kyle C. H. Chin; Sheng Wang; Andrew J. Boydston; Ramathasan Thevamaran; Padma Gopalan (Giant, 2024)
We explore the potential for using a brush-coil triblock copolymer to enhance the mechanical properties of epoxy resin for 3D printing applications. Epoxy resins are widely used in structural material and adhesive and have great potential for 3D printing. However, the highly brittle nature of epoxy resins requires the use of large concentrations of toughening agents that pose significant challenges in meeting rheological requirements of 3D printing. We report a reactive brush-coil block copolymer with three distinct blocks that can phase separate and chemically crosslink with the base epoxy resin to form spherical aggregates. Detailed scanning electron microscopy imaging shows that these aggregates can arrest and deflect cracks during propagation and can synergistically strengthen (∼ 1.5×) and toughen (∼ 2×) the epoxy resin with even 1 wt% of the BCP additive to the base resin. Importantly, both the modulus and the glass transition temperatures are preserved. Direct ink writing (DIW) and digital light processing (DLP) 3D printing of the modified resins also shows the same strengthening and toughening effects seen in mold-cast samples, demonstrating its compatibility with 3D printing processes. These findings suggest that brush-coil triblock copolymers additives at very low concentrations can synergistically improve the mechanical properties of epoxy resin for 3D printed parts.